(untitled) (Journal of the Bangladesh Agricultural University, 2020)
The study was performed to evaluate the effect of different concentrations of potassium meta-bisulphite (KMS) as preservative on nutritional and sensory quality of formulated green mango pulp stored at -20°C for 120 days. The mango pulp was formulated with the addition of sugar, salt, chilli powder, citric acid and KMS at various concentrations such as 250, 500 and 1000 ppm. The formulated pulp was intended to use as ready to drink green mango juice by diluting with three fourths to half part of water so that the final concentration of preservatives remained within the safe level (350 mg/Kg). Moisture, percent acidity and vitamin C content of all the treatments decreased slightly during storage for 120 days but ash content remained almost unchanged. During storage period, TSS, total sugar and pH of the samples increased while non-reducing sugar decreased. With regard to color parameters, L* values of the extracted green mango pulp (S1) and the formulated pulps (S2, S3, S4 and S5) were found quite close but they increased with time during storage. All the results of a* value (greenness to redness) were observed negative, which indicated the absence of red hue in all the samples till 120 days. The b* value (blueness to yellowness) was decreased with time which indicated also of yellowness of the samples during storage. The optical density of all the samples was increased with time which indicated the occurrence of non-enzymatic browning during storage. Samples treated with KMS (S3, S4 and S5) had the lower microbial load than that of unformulated samples. All the samples were found acceptable up to 120 days of storage. KMS as preservative showed no significant effect on the proximate composition of formulated green mango pulp. Regarding organoleptic taste testing, samples preserved with different concentration of KMS did not show any significant difference in terms of color, flavor, taste and overall acceptability. In conclusion, formulated green mango pulp can be used as refreshing drinks after diluting with water by storing at freezing condition for four months. J Bangladesh Agril Univ 18(3): 734–741, 2020 https://doi.org/10.5455/JBAU.105300